The influence of gender equality perception and company concern on generation z work involvement in logistics and delivery companies in Jombang - Heny Agustiningsih; Asnawi Hidayat (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to analyze the influence of gender equality perceptions and corporate concern on work engagement of Generation Z in logistics and delivery companies in Jombang Regency. The research approach used is quantitative with an explanatory research design. Primary data were collected through a Likert-based questionnaire distributed to 60 Generation Z respondents, determined using the Slovin formula from a total population of 146 employees. Data analysis was conducted using multiple linear regression with the help of SPSS version 26 software. The results showed that gender equality perceptions have a positive and significant effect on work engagement, while corporate concern has a positive but insignificant effect. Simultaneously, both independent variables were proven to have a significant effect on work engagement of Generation Z. This finding emphasizes the importance of implementing gender equality principles and strengthening organizational concern in building an inclusive and supportive work environment. The practical implications of this study encourage logistics and delivery companies to integrate fair, inclusive, and welfare-oriented human resource policies to increase work engagement and productivity of the Generation Z workforce.